Cycle Time Optimization On Imerys Using Talpac - Basirum, Muhammad Azli Azam (Universiti Sains Malaysia, 2017)
Mining and quarrying are classified as one of the major economic sectors in Malaysia. This economy sectors are increasing year by year recording to Bank Negara Malaysia. The result is increasing demand from other industries that need quarry and mining to cope with the situation to produce materials efficiently. From this study, the production of tonnage per year can be increased if the haulage are operates efficiently. Other factor also affect the productivity of the quarry operation such as excavator, haul road and operator efficiency. Study proven that independent evaluation of every excavator-truck combination is necessary to identify the optimal combination. Larger excavators may result in a lower mining cost by reducing the system operating duration. Furthermore, the optimum cycle time without neglecting safety of the operators and equipment was studied and estimated. Simulation software such as Talpac software is one of the software that estimate the cycle time and production per operating hour based on the real case study. The estimation resulted is to achieve new parameters and optimum cycle time.